The Drivers of Capital Flows in Emerging Markets Post Global Financial Crisis - Hannan, Swarnali (IMF Working Papers; Working Paper ;, 2017)
Using a sample of 34 emerging markets and developing economies over the period 2009Q3-2015Q4, the paper employs a panel framework to study the determinants of capital flows, both net and gross, across a wide range of instruments. The baseline regressions are then extended to focus on high and low episodes - quarters with flows one standard deviation above/below mean. Overall, the results suggest that the capital flow slowdown witnessed in recent years is due to a combination of lower growth prospects of recipient countries and worse global risk sentiment. However, the determinants of flows can be considerably different across instruments and across the type of flows considered, net or gross. The sensitivity of certain types of flows, towards push and pull factors, increases during periods of high and low capital flows. Moreover, some variables may not necessarily be significant during normal times, but can be important drivers during such episodes, and vice versa. Indicators like the gap between the U.S. long- and short-term maturity bond yields - not significant during normal times - can be an important driver during high episodes.